Dosage Mortality Studies with Bacillus thuringiensis and Neem Extract on Diamondback Moth, Plutella xylostella (Lepidoptera: Plutellidae) - Intan Ahmad (Universitas Gadjah Mada, 1999)
The objective of the study was to evaluate the responses of the diamondback moth, Plutella xylostella (L.) larvae to Bacillus thuringiensis and Neem extract. Therefore, dosage mortality studies using bioassay method were conducted on populations of P. xylostella from Garut, Pangalengan, and Lembang. Tests with B. thuringiensis, resulted in no significant differences in susceptibility between Garut and Pangalengan populations. However, those two populations were differed significantly in susceptibility to Lembang population which had the highest value of LC50 with resistance factor of 2.63, suggesting that a significant level of resistance against B. thuringiensis already occurred. In response to neem extract treatment, the results, as expected showed that there were no significant differences in susceptibility among the three populations. This indicates that neem extract could be used to control P. xylostella that has developed resistance to B. thuringiensis.